Implementasi E-Learning Berbasis Learning Management System Pada Program Studi Sistem Informasi Ukmc - Sri Andayani; Niken Ayu Larasati (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2019)
E-learning is learning that is arranged with the aim of using an electronic or computer system so that it can support the learning process. The use of e-learning as educational technology produces effective and efficient learning that is real and successful through LMS support. LMS is software that is used to create web- based online learning materials (e-learning) and manage learning activities and their results. The benefits of LMS felt in the use of LMS so far are the process of discipline and the increasing independence of students. By using LMS, the assessment becomes open and fair for every student, because the material resources and assignments can be accessed at any time and have their own rules. LMS has standard features, namely: (1) Uploading and sharing material; (2) Forum and Chat; (3) Quizzes and Surveys; (4) Gathering and reviewing assignment and (5) Recording grades. This study aims to implement LMS-based e-learning in the UKMC Information System Study Program. LMS that is implemented using Dokeos. The implementation of LMS Dokeos in the Information System Study Program was carried out in the Odd and Even Semester of the 2018/2019 academic year with courses that included around ten courses. All feature functionality on Dokeos has been used properly